Daya Adaptasi Mutan Padi Beras Merah dan Varietas padi Gogo di Tiga Lahan Sub Optimal di Indonesia - Eries Dyah Mustikarini (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Mustikarini et al, 2016.Â Daya Adaptasi Mutan Padi Beras Merah dan Varietas padi GogoÂ di Tiga Lahan Sub Optimal di Indonesia. JLSO 5(1):18-26.Yield trials mutant gamma irradiation results important to know the genetic stability with regard to the potential yield. Mutants adaptability in many locations and seasons that can be known whether the mutant proper grown in mosttype soil in Indonesia. This study aims to determine the ability of the mutant rice brown rice adapasi iiradiasi results of gamma rays and power yield. The research was conducted in January-December 2015. Yield trials conducted in ultisol soil, Village Balunijuk, Merawang, Bangka. Multilocation test on three location in Indonesian is Jombang, southwest Bangka, Bangka, Lampung, Batu and pontianak. The results conducted on the land southwest Ultisol, Village Balunijuk, Merawang, Bangka.In the dry season from April to October 2015. The results yield trials conducted on 6 mutant to-7 (M7) and four varieties showed MR1527 has the highest yield and is not significantly different from the varieties echo lake and Inpago 4. The test results multilocation showed that the mutants were able to adaptation in West Bangka regency ultisol land, land ultisol in Pontianak, and land grumusol in Jombang, East Java, in the dry season.